Licensure of Sheltered-Care Facilities: Does It Assure Quality? - Segal, Steven P. (Social Work (Stellenbosch), 1994)
In California, licensure was intended to assure a minimum level of quality in sheltered-care facilities for the mentally ill population. This longitudinal study relates characteristics of facilities, their residents, and communities to subsequent licensure and considers differences between licensed and unlicensed facilities at follow-up. Initial interviews were completed in 214 facilities in 1973 six months before the implementation of the California Residential Facilities Licensing Act. Follow-up interviews occurred in 1985. Results indicate that although licensure occurred with greater frequency among facilities serving the most disabled population, licensure neither predicts nor has as its apparent consequence the development of higher-quality facilities. An alternative approach to quality assurance is offered.